miR-625 down-regulation promotes proliferation and invasion in esophageal cancer by targeting Sox2 - Wang, Zhiqiang; Qiao, Qiao; Chen, Min; Li, Xianhua; Wang, Zhenjun; Liu, Chuanxin; Xie, Zongtao (FEBS letters, 2014)
•Expression of miR-625 in EC specimens was significantly lower than in corresponding adjacent tissues.•Low expression of miR-625 positively correlated with the proliferation and invasion of EC cell lines in vitro.•Direct binding of miR-625 to the Sox2 3′ UTR was demonstrated.•miR-625 overexpression diminished but miR-625 knockdown increased Sox2 expression levels in EC cells.•miR-625 is related to proliferation and invasion of EC by regulating Sox2. miR-625 has been reported to exhibit abnormal expression in esophageal cancer (EC), but the mechanism and functions of miR-625 in esophageal cancer remain unclear. miR-625 down-regulation and Sox2 up-regulation were validated by qRT-PCR in 158 EC samples. Low expression of miR-625 promotes cell proliferation and invasion, while high expression of miR-625 has the opposite effect. Sox2, a target gene of miR-625, was examined by luciferase assay and western blot. Our data suggest that miR-625 may regulate the biological processes of EC via controlling Sox2 expression.